2015
DOI: 10.4103/2229-516x.157162
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of methylphenidate and atomoxetine in oppositional defiant disorder comorbid with attention deficit hyperactivity disorder

Abstract: Background:Oppositional defiant disorder (ODD) is frequently comorbid with attention deficit hyperactivity disorder (ADHD) and is associated with substantial functional impairments. Methylphenidate and atomoxetine are well-established drugs for the management of ADHD. Some studies from Western countries have reported these drugs to be effective in the management of ODD comorbid with ADHD. This study aimed to assess if methylphenidate and atomoxetine are efficacious in treating Indian children with ODD comorbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…Surprisingly, although MPH in this study has been demonstrated to bring about improvements in ODD symptoms as reported by the parents and teachers in the study, the effects of MPH on ODD symptoms were not significantly different to those of the placebo. Several clinical trials (Garg et al 2015;Masi et al 2017;Golubchik et al 2018;Pan et al 2018;Sultan et al 2019), including ours (Shang et al 2015;Shih et al 2019), have reported that MPH is able to reduce ODD symptoms. Nevertheless, there is a significant amount of evidence available, supporting the idea that ADHD patients with ODD symptoms or an ODD diagnosis seem to benefit from the addition of atypical antipsychotics, such as risperidone (Masi et al 2017;Sultan et al 2019), quetiapine (Sultan et al 2019), and aripiprazole (Pan et al 2018;Sultan et al 2019), to their MPH treatment (Masi et al 2017;Golubchik et al 2018); these additional useful interventions also include psychosocial interventions (Abikoff et al 2004;Van der Oord et al 2008;Chan et al 2016;Suzer Gamli and Tahiroglu 2018).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Surprisingly, although MPH in this study has been demonstrated to bring about improvements in ODD symptoms as reported by the parents and teachers in the study, the effects of MPH on ODD symptoms were not significantly different to those of the placebo. Several clinical trials (Garg et al 2015;Masi et al 2017;Golubchik et al 2018;Pan et al 2018;Sultan et al 2019), including ours (Shang et al 2015;Shih et al 2019), have reported that MPH is able to reduce ODD symptoms. Nevertheless, there is a significant amount of evidence available, supporting the idea that ADHD patients with ODD symptoms or an ODD diagnosis seem to benefit from the addition of atypical antipsychotics, such as risperidone (Masi et al 2017;Sultan et al 2019), quetiapine (Sultan et al 2019), and aripiprazole (Pan et al 2018;Sultan et al 2019), to their MPH treatment (Masi et al 2017;Golubchik et al 2018); these additional useful interventions also include psychosocial interventions (Abikoff et al 2004;Van der Oord et al 2008;Chan et al 2016;Suzer Gamli and Tahiroglu 2018).…”
Section: Discussionmentioning
confidence: 77%
“…Our randomization procedure should have also diminished any period effect (Richens et al 2001;Li et al 2015). Fifth, although the efficacy of ORADUR-MPH has been demonstrated in this study and the tolerability was good, this study does not provide information about a head-to-head comparison of ORADUR-MPH with other formulations of MPH (Gau et al 2006b;Coghill et al 2013) or with atomoxetine (Garg et al 2015;Ni et al 2016Ni et al , 2017Shang et al 2016), both of which are currently used for treating ADHD. Finally, like all the MPH treatment studies, methylphenidate gives rise to several easily recognizable AEs, one such being decreased appetite; such well-known adverse effects may lead to a loss of blinding and thus influence rating of symptom, particularly when this is carried out by parents and assessors who have knowledge of reported adverse effects.…”
Section: Strengths and Limitationsmentioning
confidence: 78%
See 2 more Smart Citations
“…В ряде публикаций показана возможность экстраполяции применительно к ГРП современных терапевтических подходов для лечения СДВГ, преимущественно касающихся назначения психостимуляторов и атомоксетина. При этом указывается на бо`льшие трудности курации данной категории детей по сравнению с более «чистыми» вариантами гиперкинетических нарушений [10][11][12], необходимость применения более высоких доз лекарственных препаратов [13] и зависимость степени редукции поведенческих симптомов от выраженности общей реакции на терапию симптоматики СДВГ [14].…”
unclassified